Who's Leaving Money on the Table? Evidence from IPOs within Business Groups1. (21st June 2017) - Kim, Woojin; Lim, Chan; Yoon, Tae Jun
Abstract: This paper examines how controlling shareholders of business groups may pass on the cost of IPO underpricing to minority shareholders. Based on a sample of IPOs made in Korea, we find that sale of secondary shares in Korea in general does not reduce underpricing as it does in the US. However, we do find less underpricing or even overpricing when the offered shares are directly sold by the controlling shareholders. On the other hand, sale of secondary shares held by affiliated firms leads to a negative market reaction for the selling firms, implying a direct wealth transfer from shareholders of affiliated firms to IPO subscribers. These findings suggest that minority shareholders in certain affiliated firms, or scapegoats, may bear the cost of underpricing while controlling shareholders of the business group remain effectively protected instead.